Challenges of Halal Standards and Halal Certification for Islamic Marketing - Islam, Mohammad Mominul; Ab Talib, Mohamed Syazwan; Muhamad, Nazlida (Muslim Business and Economics Review, 2023)
Halal standards and certification continue to pose challenges for Islamic marketing. Resolving this is critical for the sector. This study uses the critical literature review (CLR) and systematic literature review (SLR) approaches by reviewing 76 published articles from Scopus-indexed journals between the years 2012 and 2023. Further, it analyses qualitative Quranic verses and content through the use of Stakeholder Theory (ST) and the ATLAS.ti qualitative data analysis software. Findings show that challenges facing halal standards and certification comprise heterogeneity, questionable raw materials, unethical practices, poor understanding of Islamic theology, communication gaps, acceptance variability, human resource management problems, supply chain obstacles, and improper Islamic marketing orientation. In addition to these common challenges, marketing problems, and poor brand positioning decisively hinder the growth potential of the halal industry. Importantly, the qualitative Quranic verses must satisfy Islamic scholars, certification boards, producers, halal marketers, and researchers to resolve the halal standards and certification-based challenges. All stakeholders must comprehend the insights arising from the general and special challenges facing the halal industry to synthesize the relevant and prescriptive Quranic verses as strategic tools. Stakeholders must further ponder future challenges regarding standards and certification on halal price, place, and promotion since current certification only focuses on products.